OPTIMIZATION, CHARACTERIZATION, AND IN VIVO HEPATOPROTECTIVE EVALUATION OF NAC-LOADED NANOPARTICLES USING QBD AND IMAGEJ® SOFTWARE - MADUPOJU, BHAVANA; ARETI, ANKARAO; MALOTHU, NARENDER; CHAMAKURI, KANTLAM (International Journal of Applied Pharmaceutics, 2025)
Objective: This study formulated four novel N-Acetylcysteine (NAC)-lipid nanoparticles (Solid Lipid Nanoparticles [SLN], Nanostructured Lipid Carriers, Nano Drug Conjugate Carriers, Polymer-Lipid Hybrid Nanoparticles) and characterised their physicochemical features and in vitro drug release pattern to enhance NAC's pharmacological capabilities. The study also designed to test optimised formulation's hepatoprotective efficacy in vivo using Image J®. Methods: The homogenisation approach was the chosen for nanoparticle preparation, which was then followed by characterisation. The optimisation process was conducted utilising the box–behnken design of Quality by Design technique. Hepatoprotective efficacy study using carbon tetrachloride (CCl₄)-induced liver damage stress mouse animal model was utilised to conduct in vivo studies to study the cellular toxicity. Results: In Fourier Transform Infrared Spectroscopy, X-ray Diffraction, and Differential Scanning Calorimetry studies, the medication and formulative components did not interact, and the lipid structure and NAC structure were unchanged. Scanning Electron Microscopy pictures show the nanoparticles' nearly spherical form and rough surface. The prepared design has an Encapsulation Efficiency (EE) of 62.56 to 86.32%. Polydispersity index ranged from 0.156 to 0.232. The SLN had a mean particle size of 96.23 to 159.10 nm. SLN had the highest release percentage (92.3) among the four varieties. Higuchi model of medication release was observed in optimised NAC-SLNs with spherical and intact chemical structure (88.95% EE, 92.35% drug release,-25.08 mv zeta potential, <200 nm of particle size). Conclusion: Lastly, the 4 types of NAC-nanoparticles showed no statistically significant changes from SLN, making them viable antioxidant drug carriers. This work designed and formulated SLN of the hepatoprotective medication to improve bioavailability and overcome limited solubility, strong protein binding, metabolising enzymes, and efflux mechanisms. The study found that NAC can treat liver ailments if placed into a proper delivery method.